Thoracic surgery during the coronavirus disease 2019 (COVID-19) pandemic in Madrid, Spain: single-centre report. (19th October 2020) - Hoyos Mejía, Lucas; Romero Román, Alejandra; Gil Barturen, Mariana; Córdoba Pelaez, Maria del Mar; Campo-Cañaveral de la Cruz, José Luis; Naranjo, José Manuel; Crolwey Carrasco, Silvana; Tanaka, Shin; Sánchez Calle, Alvaro; Varela de Ugarte, Andrés; Gómez de Antonio, David
Abstract: OBJECTIVES: We reviewed the incidence of coronavirus disease 2019 cases and the postoperative outcomes of patients who had thoracic surgery during the beginning and at the highest point of transmission in our community. METHODS: We retrospectively reviewed patients who had undergone elective thoracic surgery from 12 February 2020 to 30 April 2020 and were symptomatic or tested positive for severe acute respiratory syndrome coronavirus 2 infection within 14 days after surgery, with a focus on their complications and potential deaths. RESULTS: Out of 101 surgical procedures, including 57 primary oncological resections, 6 lung transplants and 18 emergency procedures, only 5 cases of coronavirus disease 2019 were identified, 3 in the immediate postoperative period and 2 as outpatients. All 5 patients had cancer; the median age was 64 years. The main virus-related symptom was fever (80%), and the median onset of coronavirus disease 2019 was 3 days. Although 80% of the patients who had positive test results for severe acute respiratory syndrome coronavirus 2 required in-hospital care, none of them were considered severe or critical and none died. CONCLUSIONS: These results indicate that, in properly selected cases, with short preoperative in-hospital stays, strict isolation and infection control protocols, managed by a dedicated multidisciplinary team, a surgical procedure could be performed with a relatively low risk for the patient. Abstract : Since the outbreak of the novel coronavirus disease 2019 (COVID-19) caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in Wuhan, China [1], over 4.9 million cases have been diagnosed around the world [2].